Whether the Middle Eocene Salt-Forming Brine in the Kuqa Basin Reached the Potash-Forming Stage: Quantitative Evidence from Halite Fluid Inclusions. (10th March 2021) - Xu, Yang; Cao, Yangtong; Liu, Chenglin
Abstract : The Kuqa Basin is an important potentially potash-bearing basin in China, and thick salt-bearing strata were deposited under the influence of multistage Tethyan transgression-regression cycles during the Eocene. At present, research on the process of potash formation in the Kuqa Basin has mostly focused on traditional salt mineralogy, whole-rock geochemistry, and evaporite sedimentary evolution characteristics. However, research on the original ore-forming parent fluid directly related to potash formation has not yet been carried out, directly hindering further evaluation of potash mineralization. Therefore, this paper takes the internal factors controlling potash formation as the starting point and analyzes the physical and chemical properties, such as the homogenization temperatures (T h ) and chemical compositions, of primary halite fluid inclusions. A total of 220 T h data from fluid inclusions were obtained, and the temperatures ranged from 9.4 to 54.1°C, indicating a high-temperature brine environment conducive to the rapid deposition of the potash deposit. In total, 22 halite fluid inclusions were analyzed for chemical components. The highest KCl content reached 0.59%, which was higher than the lowest industrial grade of potassium-rich brine (0.5%), indicating that the brine experienced a high degree of evaporation and concentration during the salt-forming period and reached the potash precipitation stage. This paper provides quantitative data on the evolution of the sedimentary environment in the Kuqa Basin and supports future potash exploration.